A pre-event assessment of residents' reactions to Dubai Expo 2020. (October 2018) - Tournois, Laurent
Abstract: This study uses a sample drawn from 317 residents (Emiratis and expatriates) of the city of Dubai and a two-step procedure based on structural equation modelling and a conditional process analysis to investigate 1) the direct and/or indirect effects of place dependence and place identity on residents' reactions to mega events; 2) to provide the boundary conditions for these relationships by examining the role of length of residence and gender. The findings reveal the mediating role of place identity in the relationship between place dependence and residents' reactions to mega events, while there is no evidence of the moderating role of length of residence and gender. The proposed model visualises important interrelations between human-place bonds and how they may be converted into positive and supportive reactions. Highlights: Residents' reactions to mega events and human-place bonds have received limited attention in the tourism literature. Overall residents' attitude positively influences their intention to support place marketing and tourism development. Place identity mediates the relationship between place dependence and reactions to mega-events. Length of residence and gender do not have any moderating influence. Resident-place bonds may hinder resistance to the development of urban tourism surrounding mega events.